Peran strategic thinking dalam menjaga stabilitas keamanan regional dan mewujudkan kesejahteraan nasional sesuai amanat UUD 1945 - Roedy, Roedy; Irwanto, Bambang; Taufik, Robby Mochamad (Universitas Negeri Malang, 2025)
The role of strategic thinking in maintaining regional security stability and achieving national welfare in accordance with the mandate of the 1945 Constitution Strategic thinking plays an important role in maintaining regional security stability and national welfare according to the 1945 Constitution. Indonesia plays a strategic role in multilateral diplomacy to face long-term challenges in Southeast Asia. This study uses a qualitative approach with a literature study method, analysing foreign policy and national security. The results show that strategic thinking contributes to regional stability through active diplomacy and maritime economic cooperation. The main findings include the concept of Indonesia's conceptual network in managing the South China Sea as an opportunity for economic cooperation. The novelty of this study lies in the integrative analysis of strategic thinking, diplomacy policy, and national welfare in the context of regional stability. With a data-based strategy and long-term vision, Indonesia can continue to play a role in global peace and prosperity. Pemikiran strategis berperan penting dalam menjaga stabilitas keamanan regional dan kesejahteraan nasional sesuai UUD 1945. Indonesia memainkan peran strategis dalam diplomasi multilateral guna menghadapi tantangan jangka panjang di Asia Tenggara. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka, menganalisis kebijakan luar negeri dan keamanan nasional. Hasil menunjukkan bahwa pemikiran strategis berkontribusi terhadap stabilitas kawasan melalui diplomasi aktif dan kerja sama ekonomi maritim. Temuan utama mencakup konsep conceptual network Indonesia dalam mengelola Laut China Selatan sebagai peluang kerja sama ekonomi. Kebaruan penelitian ini terletak pada analisis integratif antara pemikiran strategis, kebijakan diplomasi, dan kesejahteraan nasional dalam konteks stabilitas kawasan. Dengan strategi berbasis data dan visi jangka panjang, Indonesia dapat terus berperan dalam perdamaian dan kesejahteraan global.